The relationship between gold price and macroeconomic factors / Amirah Athileah Hizam - Hizam, Amirah Athileah (2022)
Gold is a commodity and material that play a significant role in economy. Gold is increasingly valued for its potential to endure financial crises and guard against the rising inflation of fiat currencies. Besides, most central banks primarily reserve gold compared to paper currencies as their monetary reserve. Nonetheless, an unexpected Covid-19 outbreak arises, resulting in a decreasing economy and recession. Considering that others financial instrument and macroeconomic factors went downwards, the price of gold may or may not decline as well. Consequently, the objective of this research is to investigate the four macroeconomic factors that influence the gold price. This study involved 10 years' data from 2012 to 2021 to assess the relationship between the GDP growth, stock exchange index, inflation rate and overnight policy rate. These findings will aid individual and corporate investors, policy maker, financial institution, economist and government in making the best decisions and formulating suitable regulations to make better judgments in the future.